Edge effect on orchids of a fragment of semi-deciduous seasonal forest in the Southeast of Brazil - Pedroso-de-Moraes, Cristiano; Prezzi, Lígia Eleonor; De Souza-Leal, Thiago [UNESP]; Canonici, Thiago Fernandes; Jr, Olavo Raymundo; Silveira, Paulo (My University, 2015)
The edge effect was evaluated in a semi-deciduous seasonal forest fragment of Araras, state of São Paulo, Brazil. The sampling took place in 20 parcels at 30 m from the edge and another 20 parcels at 100 m from the edge. The general shape of the forest fragment was evaluated by the calculation of the Circularity Index, and correlations were determined between biotic and abiotic factors to test for possible relationships. A total of 346 individuals, composing of nine species and nine genera, were identified. The diversity of orchids in the studied area is low, and the abundance of species in the fragment is not distributed evenly. The edge has more species and individuals, showing it to be more beneficial for the survival of orchids, especially when associated to the watercourse. This increase in the orchid population in the edge can be related to luminosity. However, the studied forest fragment has fewer orchid species than other, better conserved fragments of Semi-Deciduous Seasonal Forest.
Keywords: Diversity; Epiphytes; Forest fragmentation; Terrestrial orchids